Reconstruction of social work education in China through transformative partnership: Case study of the 30 years' partnership between The Hong Kong Polytechnic University and Peking University. Issue 1 (2nd January 2020) - Yuen-Tsang, Angelina Woon Ki; Wang, Sibin
ABSTRACT: Social work education, first introduced to the Chinese mainland in the 1920s, was eliminated from all universities in the early 1950s, but was restored to higher education institutions to respond to the growing demand for social workers in the end of 1980s to resolve escalating social problems triggered by the open-door economic policy. In this paper, the authors will present the concept of transformative partnership and discuss the evolvement of the partnership relationship between The Hong Kong Polytechnic University and Peking University during the past thirty years in fostering the reconstruction of social work education in Mainland China from 1988 to 2018 and beyond. The authors will illustrate the gradual deepening of our partnership from one which was transactional to one that is transformative in nature. The authors believe that our partnership has not only transformed the traditional paradigm of professional education in China but has also transformed all the key stakeholders involved, particularly the educators, students and service-users through the partnership process.